2008
DOI: 10.1016/j.mce.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Time dependency of uterine effects of naringenin type phytoestrogens in vivo

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 of 29A c c e p t e d M a n u s c r i p t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
1
29
2
1
Order By: Relevance
“…The strong estrogenic potency exhibited in RNDA cells is in accordance with the effects shown in other cell models and organs by our group and others [25,65,[73][74][75]. Hence, 8-PN seems to show strong affinity for both ER␣ and ER␤ [76], even though our data does not support ER selectivity in vivo.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The strong estrogenic potency exhibited in RNDA cells is in accordance with the effects shown in other cell models and organs by our group and others [25,65,[73][74][75]. Hence, 8-PN seems to show strong affinity for both ER␣ and ER␤ [76], even though our data does not support ER selectivity in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…These results are in contrast to Zierau et al, who reported a high measurable luciferase output in a dose-dependent manner in other cell models [25,65]. In addition, there are gene expression data indicating that 6-DMAN regulates the expression of several but not all ER target genes in the uterus of ovariectomized rats [25].…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations